Small-scale variability in phenological, leaf morphological properties and isoenzyme pattern of sessile oak complex (Lepidobalanus sub-genus) in a sessile oak-Turkey oak forest stand - Kanalas, Péter (Acta Biologica Szegediensis, 2008)
In this work small-scale variation of leaf morphological, phenological and isoenzyme pattern was investigated win trees belonging to the Lepidobalanus sub-genus in a sessile oak-Turkey oak stand in order to make an exact taxonomic identification for further studies on physiological tolerance to climatic fluctuations. Classification functions based on leaf morphological traits suggest that most of the trees belongs to Q. petraea, but the introgression effects of Q. dalechampii and Q. polycarpa is also significant in the forest stand which might favour the drought tolerance in these groups of trees. Two representatives (Q. pubescens, Q. virgiliana) of Lanuginosae series are also present in the forest stand. The maximum difference in budburst time was two weeks among the trees. Representatives of Lanuginosae series can be described by late budburst. The isoenzyme analysis did not reveal taxon-specific allels, but some loci exhibited considerable differences in the frequency of allels among the different series and budburst groups.